Back Cover: Chemistry of Diruthenium and Dirhodium Analogues of Pentaborane(9): Synthesis and Characterization of Metal N, S‐Heterocyclic Carbene and B‐Agostic Complexes (Chem. Eur. J. 9/2015). Issue 9 (23rd February 2015) - Roy, Dipak Kumar; Mondal, Bijan; Anju, R. S.; Ghosh, Sundargopal
<x xml:space="preserve">Abstract</x> A comparative reactivity study of two isoelectronic nido‐dimetallapentaboranes with 2‐mercaptobenzothiazole demonstrates the influence of metal change from Group 8 to Group 9. The former leads to the formation of B‐agostic, whereas the later affords a boratrane complex. In addition, the first example of a structurally characterized N, S‐heterocyclic carbene complex of rhodium is reported. For more details see the Full Paper by S. Ghosh et al. on page 3640 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>